2017
DOI: 10.1016/j.drugalcdep.2016.09.022
|View full text |Cite|
|
Sign up to set email alerts
|

Short communication: Genetic association between schizophrenia and cannabis use

Abstract: Background and aim Previous studies have shown a relationship between schizophrenia and cannabis use. As both traits are substantially heritable, a shared genetic liability could explain the association. We use two recently developed genomics methods to investigate the genetic overlap between schizophrenia and cannabis use. Methods Firstly, polygenic risk scores for schizophrenia were created based on summary statistics from the largest schizophrenia genome-wide association (GWA) meta-analysis to date. We an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 24 publications
6
54
1
Order By: Relevance
“…1,2 Despite compelling reasons for adapting evidence-based treatments for adults to include families in LMIC, the topic has received surprisingly little attention in the literature about global mental health services and implementation, with with the exception of a few studies that have involved family in the treatment of patients with psychotic disorders, 3 substance abuse, 4 and dementia. 5,6 A review 7 of community and home-based interventions for people with neuropsychiatric disorders in LMIC showed that fewer than 10% of the interventions involved family members.…”
Section: Engaging Families To Advance Global Mental Health Interventimentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Despite compelling reasons for adapting evidence-based treatments for adults to include families in LMIC, the topic has received surprisingly little attention in the literature about global mental health services and implementation, with with the exception of a few studies that have involved family in the treatment of patients with psychotic disorders, 3 substance abuse, 4 and dementia. 5,6 A review 7 of community and home-based interventions for people with neuropsychiatric disorders in LMIC showed that fewer than 10% of the interventions involved family members.…”
Section: Engaging Families To Advance Global Mental Health Interventimentioning
confidence: 99%
“…For example, studies using genetic data have found evidence possibly consistent with shared genetic aetiology between risk of psychosis and likelihood to use cannabis. 6 Di Forti and colleagues' study asks participants about their cannabis use prior to their first episode psychosis diagnosis, but it is possible that subclinical symptoms might have existed prior to cannabis initiation, meaning that associations in the opposite direction cannot be ruled out.…”
mentioning
confidence: 99%
“…Power et al (2014) found that a genetic risk score for schizophrenia predicted cannabis use in a sample of 2082 healthy individuals. Verweij et al (in press) used linkage disequilibrium (LD) score regression to investigate this association, and found evidence of a genetic correlation between lifetime cannabis use and risk of schizophrenia. This could be interpreted as shared genetic aetiology, but could also reflect a causal association between schizophrenia and risk of cannabis use (Gage et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…for schizophrenia and problematic substance use (Power et al, 2014;Carey et al, 2016;Kalsi et al, 2016;Reginsson et al, 2017;Verweij et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, recent studies have found that schizophrenia shares modest but significant genetic correlations with cannabis use (Pasman et al, 2018), alcohol use (Clarke et al, 2017), and risk preferences (Linnér et al, 2018). Similarly, several cross-sectional studies have reported that polygenic scores for schizophrenia predict alcohol, amphetamine, cannabis, cocaine, opioid, and sedative use disorders (Power et al, 2014;Carey et al, 2016;Kalsi et al, 2016;Hartz et al, 2017;Reginsson et al, 2017;Verweij et al, 2017). However, while previous studies have related genetic risk for schizophrenia to diagnosed substance use disorders or lifetime substance use, no study has considered how this genetic risk functions in the context of development.…”
mentioning
confidence: 99%